Students’ Writing Ability By Using AI Generative Tools; Diffit, Brisk, Mendeley - Yelliza; Siska; M. Khairi Ikhsan; Willy Satria (Jurnal Ilmiah Langue and Parole, 2024)
This study examines the impact of three AI generative tools—Diffit, Brisk, and Mendeley—on university students’ writing perceptions and motivation. A mixed-methods approach combined quantitative pretest and posttest assessments with qualitative insights from interviews and classroom observations. The participants, 27 students from Universitas Ekasakti Padang, were purposively sampled and randomly assigned to groups based on the AI tool used. Quantitative results revealed that the Diffit group achieved self-efficacy improvements from 80% (initial) to 90% (post-intervention), with a task value of 60%. The Brisk group showed consistently high self-efficacy (90%) and task value (90%), achieving an 80% writing proficiency score. In contrast, the Mendeley group recorded self-efficacy scores of 100% initially, dropping to 60%, but maintained a writing proficiency score of 80% due to a task value of 80%. Findings highlight self-efficacy as the most critical factor influencing writing improvement, supported by task value, intrinsic motivation, and perceived usefulness. Recommendations include integrating AI tools to build students’ confidence, aligning tasks with personal goals, and fostering intrinsic motivation. This study demonstrates the effectiveness of AI tools in enhancing writing proficiency by addressing students' cognitive, emotional, and motivational needs.